Sarak: the early Jains in Bengal - Bhattacharjee, Debashis (Kolkata: Bookland Private Limited, 2007)
This book represents an impressive achievement in anthropological field research among a group of people within Bengali society whose identity and survival represent a distinct from of world view, being influenced by Jaina ideals. The Saraks of Purulia, in adjacent districts of West Bengal and Bihar are quite evidently the descendants of Jaina Sravakas who originated in Western Indian and Were later migrants in 'rarh' Bengal. In the literature of 'Kavi Kankan chandi Mangal' dated back, the later of Sarak community was mentioned.
Introduction -- Land and People -- Ethnographic Profile -- Life Cycle Rituals and Religious Festivals -- Socio- Economic Profile -- Religion and Ethnic Identity -- Outcomes of the Findings and Concluding Remarks
Includes references and appendix
Keywords: Anthropology; Early Jains; Jains in Bengal